2018
DOI: 10.2147/cmar.s164980
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk assessment in modern radiotherapy workflow with medical big data

Abstract: Modern radiotherapy (RT) is being enriched by big digital data and intensive technology. Multimodality image registration, intelligence-guided planning, real-time tracking, image-guided RT (IGRT), and automatic follow-up surveys are the products of the digital era. Enormous digital data are created in the process of treatment, including benefits and risks. Generally, decision making in RT tries to balance these two aspects, which is based on the archival and retrieving of data from various platforms. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 99 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…8 Our results revealed that IGRT in adjuvant CFRT for localized breast cancer patients did not lead to worse overall survival or other outcomes. So it might be safe to use IGRT (usually via x-ray) regardless of the theoretical concern in cardiovascular disease or secondary cancer, 33,34 at least for selected patients with significant setup errors. However, it should be noted the radiotherapy setting and technique in prostate cancer radiotherapy in that RCT 8 was different vs the one for breast cancer in the current study [curative/definitive vs preventive/adjuvant].…”
Section: Discussionmentioning
confidence: 99%
“…8 Our results revealed that IGRT in adjuvant CFRT for localized breast cancer patients did not lead to worse overall survival or other outcomes. So it might be safe to use IGRT (usually via x-ray) regardless of the theoretical concern in cardiovascular disease or secondary cancer, 33,34 at least for selected patients with significant setup errors. However, it should be noted the radiotherapy setting and technique in prostate cancer radiotherapy in that RCT 8 was different vs the one for breast cancer in the current study [curative/definitive vs preventive/adjuvant].…”
Section: Discussionmentioning
confidence: 99%
“…The second cancer exists highly for patients who received RT, which have demonstrated by numerous clinical studies, and usually occur in volumes receiving total dose irradiation or nearby areas radiated with the doses from 2 to 50 Gy 31,32. Thyroid is known to have a low dose threshold for radiation-induced cancer, which is as low as 0.05 Gy in children and young adults 33,34. Hence, in RT treatment, second cancer for thyroid or other organs may be affected by out-of-field dose, which is likely to be highly associated with treatment facility due to leakage and scattering from head and accessories 35.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the errors are discovered in setup/treatment and during follow-up. There are still errors that are not covered by regular QA checks so individual clinics should perform a risk analysis of their own practice, classifying and learning from mistakes, to determine appropriate testing frequencies that maximize physicist time efficiency and patient treatment quality and to improve existing processes or implement new workflows [43]. The detection of errors is essential in the RT process as it minimizes the risk of repetition, activates mechanisms of correction, and instills in the staff a drive to improve the quality of daily activities.…”
Section: Radiotherapymentioning
confidence: 99%
“…Modern risk-based analyses show that many errors occurring in radiation oncology are due to failures in workflow [43,48]. Medical imaging is crucial to RT; its application, referred to as IGRT, encompasses tumor diagnosis, staging, prognosis, treatment planning, radiation targeting, and follow-up care [49].…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation